Single Stage Management of Anorectal Malformation in Male Neonates: Experience of a Tertiary Care Centre - Vinit Kumar Thakur; Zaheer Hasan; Vijayendra Kumar; Ramdhani Yadav; Sandeep Kumar Rahul; Digamber Chaubey (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2020)
Introduction: Anorectal malformation [ARM] can be treated either by staged procedures or by a single stage procedure. In the present study we have performed single stage surgery of ARM in male neonates. Materials and Methods: Retrospective review of cases of ARM operated over 4 years at Indira Gandhi Institute of Medical Sciences, Patna, and Bihar from January 2015 to December 2018 were undertaken. In this study we have compared the results of single stage repair of Anorectal malformation with that of staged procedures performed earlier. Fifty four patients of Anorectal malformation were operated by single stage procedure (category 1) this was compared with staged procedures (category 2). Forty three patients underwent primary PSARP (posterior sagittal anorectoplasty) and the remaining 11 primary APP (abdomino-perineal pull through) procedure. The result of these single stage procedures were compared with that of staged procedures (category 2) in which a total of 39 cases were operated from 2012 to 2014. Result: Mean post-operative hospital stay in category 1 was 11 days and 32 days in category 2. In category 1, 20 patients were analysed. In which PSARP procedure was done in 15 and in 5 patients APP procedure was performed. The Rest of the patients are in follow up. Kelly score was good to fair in 17 patients (85%) and poor in 3 (15%) patients. In category 2 it was good to fair in 28 (71.7%) cases and poor in 11 cases (28%). Conclusion: Single stage surgical repair of anorectal malformation in male neonates is reliable and can be safely performed. Early results are encouraging; however, a long term follow-up is required to get any definite conclusion.